1998
DOI: 10.1111/j.1600-0404.1998.tb07294.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral facial paralysis (PFP) and HIV infection in Togo

Abstract: Peripheral facial paralysis is frequently associated to HIV infection. An HIV test must be proposed to all patients with PFP in Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…A Nigerian study showed the median age of occurrence to be 35.5 years, echoing studies in European settings [14]. A Togolese study of 150 individuals showed the average age of occurrence to be 31.4+/− 8.81 years [5]. A study with similar findings as our study was from Romania where the dominant age group of occurrence was 17-30 years [15].…”
Section: Age and Bell's Palsysupporting
confidence: 84%
See 1 more Smart Citation
“…A Nigerian study showed the median age of occurrence to be 35.5 years, echoing studies in European settings [14]. A Togolese study of 150 individuals showed the average age of occurrence to be 31.4+/− 8.81 years [5]. A study with similar findings as our study was from Romania where the dominant age group of occurrence was 17-30 years [15].…”
Section: Age and Bell's Palsysupporting
confidence: 84%
“…There is no published data on the relationship between seasons and Bell's palsy in Sub-Saharan Africa generally. HIV infection has however, been associated with Bell's palsy in the tropical countries with no reports in this regard from the Sahel countries [5][6][7]. Our clinical impression was that there seems to be a link between certain seasons and a surge in the occurrence of Bell's palsy in South Africa with its high prevalence of HIV infection.…”
Section: Introductionmentioning
confidence: 76%
“…HIV should be considered in the investigation of any facial palsy, especially in endemic regions, because early treatment can reduce the morbidity associated with the disease 5,18 . In most cases, PFP in the setting of HIV is a self‐remitting condition, and there is no clinical difference between seropositive and seronegative patients 35 . Finally, bilateral PFP is a very rare entity and should always prompt investigation even in the case of apparently healthy patients.…”
Section: Resultsmentioning
confidence: 99%
“…The finding of facial nerve palsy has a reportedly high predictive value for HIV infection, at 50-100% (Di Costanzo et al, 1990;Balogou, Kpemissi, Nack-Nack, Anani, Agboli, Prince & Grunitzky, 1998;Casanova-Sotolongo & Casanova-Carrillo, 2001). It usually presents early in the course of HIV infection and, as displayed in this study group, is usually the first manifestation of HIV infection in affected subjects (Chilla, Booken & Rasche, 1987;Brown, Thompson, Goh, Forster & Swash, 1988;Murr & Benecke, 1991).…”
Section: Discussionmentioning
confidence: 95%